Cervicogenic Dizziness in an 11-Year-Old Girl: A Case Report - Chu ECP; Wong AYL (Dove Medical Press, 2021)
Eric Chun-Pu Chu,1 Arnold Yu-Lok Wong2 1New York Chiropractic and Physiotherapy Centre, Hong Kong SAR, People's Republic of China; 2Department of Rehabilitation Sciences, The Hong Kong Polytechnic University, Hong Kong SAR, People's Republic of ChinaCorrespondence: Eric Chun-Pu ChuNew York Chiropractic and Physiotherapy Centre, 41/F Langham Place Office Tower, 8 Argyle Street, Hong Kong SAR, People's Republic of ChinaTel +852-3594-7844Fax +852-3594-6193Email eric@nymg.com.hkAbstract: Cervicogenic dizziness (CGD) is a syndrome of neck pain accompanied by a false sensation of unsteadiness and dizziness due to neck pathology. An 11-year-old girl presented with neck pain and dizziness for four months. According to the patient's statement, her complaints were likely related to the prolonged smartphone use for texting. Sagittal radiograph showed cervical kyphosis, anterior wedging of several vertebrae, and mild anterolisthesis of C2 on C3 and C3 on C4. These findings might be present in as physiological variants in children. However, continuous static stress in the minor variants could aggravate biomechanical problems, such as cervicogenic dizziness. After ruling out other neurological or vestibular problems, a multicomponent approach consisted of thermal ultrasound therapy, cervical manipulation, and intermittent motorized cervicothoracic traction to release cervical complaints. Three months later, the patient reported a resolution of neck pain and dizziness. At 12-month follow-up, all radiographic metrics showed improvement, including restoration of cervical alignment and lordotic curvature. The immature growing cervical spine has unique anatomic, physiologic and biomechanical features. A static neck flexion can lead to typical injury patterns seen in this age group. This article aims to raise awareness of the potential harms of excessive smartphone use by children.Keywords: anterolisthesis, cervical kyphosis, cervicogenic dizziness, children, excessive smartphone use, neck pain